Ismayilov , Alishir - (:unkn) unknown (My University, 2026)
Alishir Ismayil oglu Ismayilov graduated from the Moscow Institute of Geodesy, Aerial Photography and Cartography (MIIGAiK) in 1979 with a degree in Astronomical Geodesy. He began his professional career as an Engineer at the Institute of Geography of ANAS and joined the Azerbaijan University of Architecture and Construction (AzUAC) in 1980. He has held academic positions at the Department of Engineering Geodesy, now the Department of Geomatics, and currently serves as a Senior Lecturer. In 1986–1987, he conducted research at the Space Research Scientific-Production Association. From 2003 to 2005, he participated in the Baku–Tbilisi–Ceyhan (BTC) oil pipeline project, providing geodetic support for the construction of intermediate stations. From 2005 to 2015, he was involved in the redesign and planning of the Silk Road highways, collaborating with international engineering companies. His current research focuses on geodetic support systems for transnational infrastructure projects. He is the author of 24 scientific articles, 15 conference papers, 6 methodological guidelines, 6 course programmes, and 4 theses.